2007
DOI: 10.1029/2006wr005653
|View full text |Cite
|
Sign up to set email alerts
|

Mountains of the world, water towers for humanity: Typology, mapping, and global significance

Abstract: [1] Mountains are important sources of freshwater for the adjacent lowlands. In view of increasingly scarce freshwater resources, this contribution should be clarified. While earlier studies focused on selected river systems in different climate zones, we attempt here a first spatially explicit, global typology of the so-called ''water towers'' at the 0.5°Â 0.5°resolution in order to identify critical regions where disproportionality of mountain runoff as compared to lowlands is maximum. Then, an Earth systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
634
0
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,003 publications
(702 citation statements)
references
References 34 publications
3
634
0
10
Order By: Relevance
“…Climate change will also decrease water availability in lowlands that are influenced by discharge from contiguous mountain (Messerli et al 2004). Relatively high mountain run-off can be found in semi arid and arid regions, such as the Himalayas, but also in some humid regions, such as the European Alps (Viviroli et al 2007). We can thus say that mountains are important for the hydrology of the lowlands, especially when lowlands are arid, as is the case with the Himalayas (Viviroli and Weingartner 2004;Messerli et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change will also decrease water availability in lowlands that are influenced by discharge from contiguous mountain (Messerli et al 2004). Relatively high mountain run-off can be found in semi arid and arid regions, such as the Himalayas, but also in some humid regions, such as the European Alps (Viviroli et al 2007). We can thus say that mountains are important for the hydrology of the lowlands, especially when lowlands are arid, as is the case with the Himalayas (Viviroli and Weingartner 2004;Messerli et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mountain ecosystems cover approximately 41 % of Europe's territory, providing various services due to their multifunctionality. Mountains are "water towers" as they provide water for multiple uses, including irrigation, human consumption, and hydropower (Viviroli et al 2007). Mountain systems supply cultural services, holding spiritual value to local inhabitants, and are recreation and ecotourism attractions (Price et al 1997).…”
Section: Wilderness and Ecosystem Servicesmentioning
confidence: 99%
“…In humid climates with a tropical influence, the average value of the coefficient even fell below 1.0. In a worldwide study, Viviroli et al (2007) found that the hydrological and ecological significance of the world's mountain regions could be classified as being of essential (23% of the world's mountain area), supportive (30%), occasional (28%) or limited (19%) importance.…”
Section: Introductionmentioning
confidence: 99%
“…is equal to, or greater than, 1000 m. In a global-scale study by Viviroli et al (2007), all areas over 1000 m a.m.s.l. were included as mountain regions, as were those between 200 and 1000 m whose relief roughness exceeded 20‰.…”
Section: Introductionmentioning
confidence: 99%